1951
DOI: 10.1037/h0055263
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of the validity and rationale of the forced-choice technique.

Abstract: According to a paper by Staff, Personnel Research and Procedures Branch, the Adjutant General's Office (5), the basic idea for the forcedchoice technique was developed by Paul Horst with reference specifically to personality scales. Robert Wherry developed a similar idea while working on personality measurement for the Civil Aeronautics Author-it}', and later the Staff of the Personnel Research Section of the Adjutant General's Office attempted to apply the concept first to the design of personality inventorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1960
1960
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…For example, participants may find the faces from which to choose to be equally attractive or equally unattractive, but the forced-choice method does not permit this response. The literature is replete with evidence of problems with the reliability of forced-choice methods used in assessments of personality, achievement motivation, personnel decisions, knowledge, and vocational choices (Grosse & Wright, 1985;Jackson, Neill, & Bevan, 1973;Nederhof, 1985;Ray, 1980Ray, , 1982Travers, 1951). The problems of reliability result from forcing individuals to make decisions that were not necessarily accurate characterizations of the person being rated (i.e., overestimating or underestimating the quality of the individual being rated; Travers, 1951).…”
Section: Methodsmentioning
confidence: 99%
“…For example, participants may find the faces from which to choose to be equally attractive or equally unattractive, but the forced-choice method does not permit this response. The literature is replete with evidence of problems with the reliability of forced-choice methods used in assessments of personality, achievement motivation, personnel decisions, knowledge, and vocational choices (Grosse & Wright, 1985;Jackson, Neill, & Bevan, 1973;Nederhof, 1985;Ray, 1980Ray, , 1982Travers, 1951). The problems of reliability result from forcing individuals to make decisions that were not necessarily accurate characterizations of the person being rated (i.e., overestimating or underestimating the quality of the individual being rated; Travers, 1951).…”
Section: Methodsmentioning
confidence: 99%
“…A point may be made concerning the negative weight attributed to DI in the multiple prediction. Travers (1951) has criticized the forced-choice technique in that it does not actually control for bias-since all that one needs to do to fake a rating is to rate someone who would score high rather than the person intended for rating. Although this may be a way of faking a response on a forced-choice scale, the negative prediction weight given the DI for this study indicates that this procedure was not used in this situation for faking the scale.…”
Section: Discussionmentioning
confidence: 99%
“…Travers (1951) has suggested that forced-choice tests require the subjects to choose among alternatives none of which may be relevant for him. In defense of the forced-choice technique it is generally assumed that, if all alternatives are inappropriate, subjects will choose randomly among them as they are of equal social desirability ; this has the effect of increasing error variance but reducing &dquo;bias.&dquo; Results of the present study, however, suggest that when all alternatives are inappropriate (or equally appropriate) subjects may select the alternative which has the greatest personal social desirability.…”
Section: Ditewsionmentioning
confidence: 99%